Benzoic acid-assisted substrate-free synthesis of ultrathin nanosheets assembled two-dimensional porous Co3O4 thin sheets with 3D hierarchical micro-/nano-structures and enhanced performance as battery-type materials for supercapacitors. (1st August 2019) - Zhu, Jikui; Huang, Biao; Zhao, Chenglan; Xu, Hong; Wang, Suna; Chen, Youpeng; Xie, Li; Chen, Lingyun
Abstract: Two-dimensional (2D) porous materials have been proved to be meritorious for supercapacitors (SCs) due to unique properties of large surface area, superior intrinsic porosity and high electrical conductivity. In this work, we reported for the first synthesis of 2D porous Co3 O4 thin sheets assembled by ultrathin nanosheets via direct hydrothermal decomposition of aqueous solution of cobalt nitrate in the presence of benzoic acid (BA) without any template or surfactant . High specific capacity (497, 598.5 and 399 C g −1 at 1.0 A g −1 ) and remarkable cycling stability (9.8, 6.3 and 13.1% loss over 8000 cycles at 10.0 A g −1 ) were achieved in a three-electrode system for the Co3 O4 thin sheets at 200 °C for 6, 12 and 24 h with different specific surface area of 69.96, 142.15 and 42.07 m 2 g −1, which can be attributed to the special structural feature of an open and porous surface layer and the synergistic effect of 2D and 3D structure that significantly facilitates fast electron transport, ion diffusion and intimate electrode/electrolyte contact. Furthermore, an assembled asymmetric supercapacitor (ASC, Co3 O4 thin sheets//activated carbon (AC)) can reach a working output potential difference of 0–1.6 V with a maximum energy density of 22.49 Wh·kg −1 at the power density of 800 W kg −1 with excellent cyclic stability (only 8.2% loss of its initial specific capacity value over 10000 cycles). The results show that our synthesis provides a new insight into the fabrication of 2D hierarchical porous Co3 O4 thin sheets; in addition, the as-synthesized Co3 O4 thin sheets have potential for various applications in SCs, electrochemical sensing, and lithium ion battery. Graphical abstract: Image 1 Highlights: Two-dimensional Co3 O4 thin sheets are prepared by a simple Benzoic acid-assisted hydrothermal method. Nanoflake array-assembled porous sheets with high BET specific surface area. The Co3 O4 thin sheets-based electrode shows an ultrahigh specific capacitance and superior cycling performance. The assembled asymmetric supercapacitor exhibits a high energy density and high power density.